Kandahar in the Nineteenth Century - Trousdale, William B. (Middle East and Islamic Studies E-Books Online, Collection 2021, ISBN: 9789004441286., 2021)
This comprehensive history of nineteenth century Kandahar, Afghanistan's second largest city, uses not only traditional historical sources, but unpublished diaries, archived military reports, contemporary photographs, drawings, paintings, and maps of the city drawn by British soldiers, other European visitors, and Asian sources. In addition to its detailed expansion on familiar political history, he addresses the social structure, tribal and ethnic composition, religious institutions, and economic activity during this century. Central to his work is an often street-by-street description of the geographical layout of Kandahar, its key features, and how they changed over time. Both for historians and those seeking the context of contemporary issues in Central Asia, Trousdale's work is an essential read.